2012
DOI: 10.1038/ki.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the epidermal growth factor receptor in renal proximal tubule epithelial cells delays recovery from acute kidney injury

Abstract: To determine the role of epidermal growth factor receptor (EGFR) activation in renal functional and structural recovery from acute kidney injury (AKI), we generated mice with a specific EGFR deletion in the renal proximal tubule (EGFRptKO). Ischemia–reperfusion injury markedly activated EGFR in control littermate mice; however, this was inhibited in either the knockout or wild-type mice given erlotinib, a specific EGFR tyrosine kinase inhibitor. Blood urea nitrogen and serum creatinine increased to a comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 36 publications
4
109
0
Order By: Relevance
“…Because no difference in the rate of cell proliferation was detected in the absence of ischemic stress, we hypothesize that the antiproliferative effect of Mfn2 is evident only in the presence of signals that activate Ras/ERK. The observation that Ras and ERK are activated by renal ischemia 36 in response to multiple growth factors, including hepatocyte growth factor, 37 EGF, 14 PDGF, 38 TGF-b, 31 and IGF, 39 support this contention. Importantly, an established ERK inhibitor completely prevented the increase in ERK activation ( Figure 6, C and D) and cell proliferation ( Figure 5) caused by Mfn2 deficiency.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Because no difference in the rate of cell proliferation was detected in the absence of ischemic stress, we hypothesize that the antiproliferative effect of Mfn2 is evident only in the presence of signals that activate Ras/ERK. The observation that Ras and ERK are activated by renal ischemia 36 in response to multiple growth factors, including hepatocyte growth factor, 37 EGF, 14 PDGF, 38 TGF-b, 31 and IGF, 39 support this contention. Importantly, an established ERK inhibitor completely prevented the increase in ERK activation ( Figure 6, C and D) and cell proliferation ( Figure 5) caused by Mfn2 deficiency.…”
Section: Discussionsupporting
confidence: 55%
“…After renal ischemia, extracellular regulated kinases (ERK) have been implicated in promoting cell proliferation and repair. [14][15][16] Although in vitro studies, including our own, provide a strong link between mitofusins and PT cell apoptosis, 1,4 the hypothesis that mitofusins regulate ischemic AKI in vivo has not been directly tested. On one hand, selective deletion of Mfn2 in the PT might aggravate ischemic AKI by increasing renal cell apoptosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we recently reported increased expression of the EGFR ligand, HB-EGF, in diabetes that was mediated by endothelial dysfunction, and endothelial-specific HB-EGF deletion reduced progression of diabetic nephropathy. 34 Previous studies by us and others indicated that activation of EGFR contributes to recovery from AKI [35][36][37] by accelerating tissue regeneration but is detrimental in response to chronic kidney insults by increasing profibrotic pathways. We suggest that mild or moderate AKI induces acute and self-limited EGFR activation to promote cell repair and proliferation, whereas more severe AKI or a continuous chronic kidney injury will induce continued EGFR activation, which in turn will activate TGF-b and other signaling pathways mediating progressive renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of receptors involved in AKI-mediated injury include the FAS receptor and TGFb receptor. 40,41 Examples of receptors involved in epithelial cytoprotection and repair include the EGF receptor, 42 HGF receptor (c-Met), 43 sphingosine-1-phosphate receptor, 44 and netrin-1 receptor. 45 Many questions relating to the role of receptors in AKI remain unanswered, including the sources of the putative ligands, mechanisms of receptor activation, and signaling pathways involved in protection from injury or involved with epithelial repair.…”
Section: Receptorsmentioning
confidence: 99%